2011
DOI: 10.1007/s10681-011-0385-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of allelic variations in glutenin on the quality of pan bread and white salted noodles made from Korean wheat cultivars

Abstract: Dough rheological properties and end-use quality were evaluated to determine the effects of Glu-1 and Glu-3 alleles on those characteristics in Korean wheat cultivars. SDS-sedimentation volume based on protein weight was positively correlated with mixograph parameters and maximum height of dough and also positively correlated with bread volume, crumb firmness and springiness of cooked noodles. Protein content was negatively correlated with optimum water absorption of noodle dough, lightness of noodle dough she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 40 publications
6
23
1
1
Order By: Relevance
“…This was consistent with previous reports in which Glu-A3e was associated with lower extensibility and Rmax than Glu-A3d , A3b and A3c [33]. The negative effect of Glu-A3e on dough rheological properties was reported in several studies previously [24,33,37,38]. No unique i-type protein band was detected from the Glu-A3e allele using SDS-PAGE (Figure 1a) [39].…”
Section: Lmw-gs Alleles and Bread-making Qualitysupporting
confidence: 92%
See 1 more Smart Citation
“…This was consistent with previous reports in which Glu-A3e was associated with lower extensibility and Rmax than Glu-A3d , A3b and A3c [33]. The negative effect of Glu-A3e on dough rheological properties was reported in several studies previously [24,33,37,38]. No unique i-type protein band was detected from the Glu-A3e allele using SDS-PAGE (Figure 1a) [39].…”
Section: Lmw-gs Alleles and Bread-making Qualitysupporting
confidence: 92%
“…The five Glu-D3 alleles produced similar values for almost all quality properties in the present study (Figure 6; Table 2), which confirmed previous reports that Glu-D3 alleles produced similar Rmax and extensibilities among large collections of wheat varieties [24,33,48], although some studies indicated different effects of Glu-D3 alleles on dough strength or mixing properties [27,29,38,49]. Glu-D3a , D3b , D3c and D3d contained similar 2D-PAGE spot patterns, and all six active genes were highly conserved among the alleles (> 99% identities).…”
Section: Lmw-gs Alleles and Bread-making Qualitysupporting
confidence: 91%
“…Several studies on the relationship between protein and wheat processing quality have been reported (Payne et al 1987;Martin et al 2004;Park et al 2003Park et al , 2011Zhang et al 2009;Deng et al 2013a). Starch plays an important role in determining the processing quality (Nakamura et al 1993;Morita et al 2002;Yamamori and Quynh 2003;Yamamori 2009), and its development also affects wheat grain yield (Jenner 1994;Wardlaw et al 1989;Hurkman et al 2003;Tetlow et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of protein, that is, low molecular weight glutenin fraction is responsible for surface firmness of cooked noodles. Scientists also observed the similar effects of wheat cultivars in Korean dry noodles (Park et al 2011;Heo et al 2012).…”
Section: Factor Affecting Quality Of Yellow Alkaline Noodlesmentioning
confidence: 79%
“…Similarly, the milling industries are also responding with better quality of the wheat flour. Moreover, the engineering companies dealing in equipments and processing tools are also modifying the processing in order to maximize the returns for all stakeholders (Konik et al 1994;Okusu et al 2010;Park et al 2011). …”
mentioning
confidence: 99%